2007
DOI: 10.1021/ja075547t
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes with Vinyl, Styryl, and Vinylpyrenyl Ligands:  A Case of Non-innocence in Organometallic Chemistry

Abstract: We herein describe a systematic account of mononuclear ruthenium vinyl complexes L-{Ru}-CH=CH-R where the phosphine ligands at the (PR'3)2Ru(CO)Cl={Ru} moiety, the coordination number at the metal (L = 4-ethylisonicotinate or a vacant coordination site) and the substituent R (R = nbutyl, phenyl, 1-pyrenyl) have been varied. Structures of the enynyl complex Ru(CO)Cl(PPh3)2(eta1:eta2-nBuHC=CHCCnBu), which results from the coupling of the hexenyl ligand of complex 1a with another molecule of 1-hexyne, of the hexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
121
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 83 publications
21
121
0
Order By: Relevance
“…44 In these species, the vinyl ligands contribute more strongly to, or even dominate, the anodic oxidation processes, and experimental findings are fully supported by quantum chemical calculations. For example, a small deviation of <g> from g e and small Dg (< 0.05) values are usually observed at 77 K. It was also found that extending the conjugation within the vinyl ligand gradually modifies the nature of the frontier orbitals and thus the anodic redox processes from fully delocalised across the metal-vinyl entity to ligand dominated with smaller, yet still detectable, metal contribution.…”
mentioning
confidence: 68%
“…44 In these species, the vinyl ligands contribute more strongly to, or even dominate, the anodic oxidation processes, and experimental findings are fully supported by quantum chemical calculations. For example, a small deviation of <g> from g e and small Dg (< 0.05) values are usually observed at 77 K. It was also found that extending the conjugation within the vinyl ligand gradually modifies the nature of the frontier orbitals and thus the anodic redox processes from fully delocalised across the metal-vinyl entity to ligand dominated with smaller, yet still detectable, metal contribution.…”
mentioning
confidence: 68%
“…Plots of the HOMO, LUMO and LUMO+1 for 4b´ which are representative of the key molecular orbitals across the series are given in Figure 7, whilst orbital energies and composition of selected important frontier orbitals are summarised in (Ar = Ph, Py) have been computed by Winter and his team [18]. Thus, in each case, the HOMO is predominately comprised of a Ru-CH=CH-Ar -type system and can be termed a "metal-ligand" (ML) orbital ( Figure 7, Table 7).…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…It has now been firmly established that ruthenium alkynyl complexes Ru(CCR)(PP)Cp´ (P = phosphine, PP = bis(phosphine); Cp´ = Cp, Cp*) [13][14][15] and Ru(X)(CCR´´)(PP) 2 made progressively lower and lower in energy (e.g. 1-naphthyl, 9-anthryl, ethynylphenyl) [18][19][20], and when incorporated into bridging ligands spanning two strongly electron-donating ruthenium fragments [21][22][23][24][25][26][27][28]. 6 The complexes Ru(CH=CHR´´)(Cl)(CO)(PR 3 ) 2 L, which are readily prepared by insertion of an alkyne into the Ru-H bond in RuHCl(CO)(PR 3 ) n (n = 2, 3) [29] offer an entry point to a wide range of vinyl complexes through facile substitution reactions of the supporting phosphine and chloride ligands by a wide range of neutral and anionic mono and bidentate ligands (Scheme 1) [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruthenium (and to a lesser extent osmium) alkenyl complexes 7 4c,i,5,15i,s,18 The facile generation of the alkenyl complexes themselves from insertion of both terminal and internal alkynes into the Ru-H bond allows for the introduction of alkenyl substituents known for their electrochemical (ferrocene) 4c or photophysical (pyrene) 19,20 properties, for example. This route has been exploited by Winter and co-workers to join ruthenium alkenyl centers within a conjugated system.…”
mentioning
confidence: 99%